Legal Protection Against Buyer Good Faith in Implementation Execution of Mortgage Rights - Jamaluddin Sasa, Dhiya Salsabila; Zainuddin, Zainuddin; Arif, Mohammad (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This journal aims to analyze the implementation of execution seizure of mortgage rights related to good faith buyers, as well as the legal protection available to them. Using normative legal research methods, the data collected includes primary, secondary, and tertiary data, with a case study on. The results of the study indicate that execution seizure by the court does not harm legitimate buyers, who still have the right to ownership even though they transact with sellers who are not entitled. The decision emphasizes the importance of legal protection for good faith buyers in accordance with the provisions of the Civil Code and the circular of the Supreme Court. It is recommended that the sale and purchase of land rights be carried out before a PPAT and that banks be more careful in providing credit to reduce future risks, and agreements between the parties must be clearly drafted to ensure legal validity.